Plan estratégico que sustente la declaratoria como destinos turísticos priorizado a los cantones Pedernales, Jama, San Vicente, Sucre - Guadamud Zambrano, Graciela del Jesús (2019)
This research was aimed to develop a plan to support the declaration as a tourist prioritized destination for the cantons of Pedernales, Jama, San Vicente and Sucre, in the Province of Manabí, Ecuador. The study embodies a mixed approach (qualitative and quantitative), with the use of bibliographic research and field observation techniques at the exploratory-descriptive level. The study is composed of three phases; the first consisted of the diagnosis of the current situation and the social environment, as well as bibliographical publications and observation visits. Tourist diagnosis sheets, inventories, cadastres, surveys, interviews to municipal officials, strategic SWOT and a matrix of involved parties were used. The second phase was an analysis of the issued regulations, prior to and post- earthquake occurred on 16 April 2016, so that supports the request in favor of the declaration of Pedernales, Jama, San Vicente and Sucre cantons as Prioritized Tourist Destination, further the analysis of the legal and institutional framework was done to foment the project, as bibliographic review techniques and analysis of official documents were used for this purpose. In the third phase of the procedure, the Strategic Plan for Tourist Management in the Area is established. As a result, the articulation between public and private entities is expected, with the identification of the regulations for the prioritized tourism destination declaration. Finally, a matrix of strategies with 10 programs and 20 projects with intervention actions was done to enhance natural and cultural resources, public, private and community efforts, as well as human talent, and technological innovations, which allow the reactivation of the study area.